Self-Regulated Learning and Students Beliefs about Self-Efficiancy (Training and Practice : Journal of Educational Sciences, 2007)
Due to the lifelong learning paradigm, but also to the results of OECD Programme for International Student Assessment (PISA) 2000, 2003, revealing the nature of learning process became an important research topic. The results showed that effective learning and school achievement strongly depends on students learning characteristics and especially the level of self-regulated learning. It became obvious that a successful instiuction needs extensive informations about the learning process and those factors which define it. A researcher group composed by teachers and PhD students designed a research with the intention to come to know the learning characteristics of Hungarian students on three level of education (primary-school, high school and university). The paper briefly introduces the conceptional background of the mentioned research, the interpretation of selfregulated learning after that details a portion of the research’s result regarding the students self-regulated learning. The paper points out the specific relationship between self-regulated learning and the students beliefs about their self-efficacy in school. The students conceptions about their efficacy in school assignments, their thoughts about the reasons of their learning failure could be an important base for organizing a learning environment which promotes effective learning.